Preservation of structural identifiability in expanded systems. (March 2018) - Jedidi, Safa; Bourdais, Romain; Lefebvre, Marie Anne
Abstract: The main result presented by this paper is that the structural identifiability of an original continues-linear time invariant (LTI) dynamic system can be preserved in expanded systems within the inclusion principle when using block structured complementary matrices. This preservation is ensured only for some selections of specific complementary matrices. Overlapping expansions of these systems are then discussed. An original system composed of two overlapped subsystems is used as a general prototype case. An illustrative example is given.